Cantares : canticles and poems of youth, 1925-1932 - Chavez, Angelico, 1910-1996 (Recovering the U.S. Hispanic Literary Heritage Project publication., 2000)
This collection, published as part of the Recovering the U.S. Hispanic Literary Heritage Project, makes available for the first time poems written between 1925 and 1932. This is an unknown work from a major figure in New Mexico letters and history.